Gene receptor polymorphism as a risk factor for BMD deterioration in adolescent girls with anorexia nervosa. (July 2013) - Stergioti, E.; Deligeoroglou, E.; Economou, E.; Tsitsika, A.; Dimopoulos, K. D.; Daponte, A.; Katsioulis, A.; Creatsas, G.
Abstract Anorexia nervosa is a serious eating disorder that is associated with decreased bone mineral density and greater lifetime risk for fractures. This case-controlled study, analyzed single nucleotide polymorphisms of genes encoding vitamin D receptor, estrogen receptor alpha (ESR1), collagen type I and calcitonin receptor (CTR). Relationships between genotype and body mass index, cycling status and lumbar spine bone mineral density (LBMD) were determined in 40 adolescent girls with anorexia nervosa and 10 age-matched controls. The distribution of CTR-AluI genotypes differed between groups, but this polymorphism was not associated with LBMD Z-score. Distribution of ESR1-XbaI genotypes did not differ between groups, but the AA genotype was associated with decreased LBMD Z-score (≤−1) (OR = 24.79, 95% CI, 1.01–606.08). Carriers of the A allele were more likely to have decreased LBMD Z-scores compared with carriers of the G allele (OR = 4.12, 95% CI, 1.23–13.85, p = 0.022). In conclusion, our study shows that anorexic patients with wild-type genotype ESR-XbaI receptor are in greater risk for decreased BMD in relation to those with the mutated gene. Prompt recognition of these patients is crucial because early administration of the proper therapeutic treatment may contribute to the prevention of adverse sequelae on bone metabolism.